Gender Mainstreaming: UNSCR 1325 as a Global Response to Mainstreaming Women in Peace Building, its Challenges and the Role of Religious Leaders - Bulus, Bullama Samuel (Kashere Journal of Politics and International Relations, 2023)
This study examines “Gender Mainstreaming: UNSCR 1325 as a Global Response to Mainstreaming Women in Peace Building, its Challenges and the Role of Religious leaders. This resolution has sought to mainstream women in peace building by requiring greater recognition of their unique needs and experiences. With secondary data, this paper discussed Resolution 1325 as a global response to mainstreaming women in peace building, its challenges and the role of religious leaders in achieving its objectives. The paper observed that despite the positive intents of Resolution 1325, several challenges are militating against achieving its objectives. Some of these challenges include impunity and widespread of sexual and gender-based violence despite increase in training and legislation; low levels of women in peace negotiations; and limited gains in female uniformed personnel among security sector institutions and low advocacy on women involvement in peace building. Therefore religious leaders should be involved in the implementation of UNSCR 1325 for a better result. The paper recommended that the United Nations should develop stringent punitive measures against perpetrators of sexual and gender-based violence for both preventive measures and deterrence; international and local organizations should work toward ameliorating representation imbalance through gender-sensitive programming, legal activism and sustained lobbying/advocacies.. Additionally, religious leaders should be equipped with necessary skills and knowledge to advocate of gender mainstreaming and peace building. The paper concluded that UN needs to ensure effective implementation of the components of the Resolution 1325 through the involvement of religious leaders because of their influence in the society.